Nursing schools and courses in history the profession in Brazil (1890-1922) - Fernando Porto; Wellington Mendonça de Amorim (Universidad de Alicante, 2012)
Central approach study, analysis and discussion about the initiatives and embodiments of nursing schools and courses, whose temporary delimitation and geographical 1890-1922 is the axis Rio de Janeiro and Sao Paulo (Brazil). The theoretical concept was that of professionalism, according to Norbert Elias. Methodologically, the written documents used were originally from the medical press and institutional reports, detailed on the knowledge production of articles, dissertations and theses. The results pointed to a total of seventeen initiatives and embodiments of schools and nursing courses before the introduction of modern nursing in Brazil, through the School of Nursing, Department of Public Health at the beginning of health reform, led by Carlos Chagas.